ANALISIS DAMPAK ILLEGAL FISHING TERHADAP PRODUKSI TANGKAPAN NELAYAN PERAIRAN UMUM DI KABUPATEN BARITO KUALA KALIMANTAN SELATAN - Fatimah Fatimah; Idiannor Mahyudin; Erma Agusliani (EnviroScienteae, 2016)
This study aims to (1) analyze the institutional capacity of fisheries surveillance in Barito Kuala regency; (2) analyze community participation in addressing the problems of illegal fishing; and (3) comparing the level of income of fishing communities before and after the formation of Pokmaswas against illegal fishing in Barito Kuala regency. The study activities carried out at Jejangkit Pasar Village, Jejangkit District, Barito Kuala Regency, South Kalimantan, with the object of research of Pokmaswas Berkat Bersama. The data collected were data sourced directly from the observation in the study location and other supporting data related to the study object. Data analyzed with descriptive and paired t – test to compare the capture production before and after illegal fishing.  The results showed that Barito Kuala regency had facilities that were intended for fish resource monitoring through patrols, conducting enforcement by regulatory authorities for fisheries, socialization of surveillance system of society based (SISWASMAS) but violations still occurred so that they gave the impression of ineffectiveness or not optimal surveillance activities undertaken in the prevention and treatment of illegal fishing, due to the lack of public understanding factors as well as economy factors. The level of participation of fishermen of Pokmaswas Berkat Bersama in the supervision of fishery resources was quite high, judging from the attitude of fishermen of Pokmaswas Berkat Bersama who mostly reported to the supervising apparatus when they saw illegal fishing activities, rebuked and advised, and ever discussed the issue of illegal fishing with their friends and were willing if they are involved in a meeting that discussed the illegal fishing. Results of the statistical analysis showed highly significant differences in capture production between before and after the occurrence of illegal fishing, where the fishermen average capture production of Pokmaswas Berkat Bersama of 2005 was 12.631 kg;  after illegal fishing in 2014 it was 3.642 kg, so it was decreased by 58%.